Dos minerais aos materiais de arquitetura e processos de degradação: edifícios e ornamentos metálicos dos séculos XIX e XX em Belém do Pará - PALÁCIOS, Flávia Olegário (Universidade Federal do Pará, 2018)
The use of iron in architecture was intensified during the second half of the XVIII century in Europe, and its influence spread over many countries in growth, such as Brazil. Belém (PA) was one of the cites that received the larger amount of building and ornaments imported, especially from England, France, Belgium and Portugal, during the XIX e XX centuries. Currently, Belém holds the largest number of iron architecture heritage remnants in the country. Despite of having great importance in construction techniques, many of these buildings were disassembled and remain on the wait for restoration processes. Also, studies about theses constructions only focus on historical and visual discussion, with no understanding of construction materials, causing empirical restoration processes. The knowledge about these materials is important to the detailed study of historical metal alloys, and different fabrication techniques, as well as weathering action, aiming future restoration processes with scientific bases. The main objective of this research is to understand the historical metals, their diversity in iron architecture and fabrication processes, and also weathering action in iron buildings and ornaments from the XIX and XX centuries in Belém. Thus, the following specific objectives were established: a) physical, chemical and mineralogical characterization of alloys and pathologies; b) identification of different kinds of alloys, in order understand the production types; c) determination of metallurgy evolution imported to the Amazon. The materials chosen for this research came from three different sites, due to their representativeness and diversity of pieces and origin: Mercado de Ferro do Ver-o-Peso building; the former chalet from the State’s Press; and the ornaments from tombs and mausoleums of the Soledade Cemetery. The methods used were Scanning Electron Microscopy (SEM) for physical characterization and punctual chemical analysis; and X-Ray Diffractometry (XRD) for mineralogical analysis. The results were presented in three scientific papers indicating: 1) iron alloys mostly composed by ferrite; 2) textural variations exhibiting four types for the building group: nodular cast iron, gray cast iron type E, wrought iron and gray cast iron type B; 3) three classification of gray cast iron for the ornamental group of diverse origins, among A, B and D; 4) corrosion as main weathering action, and products constituted by goethite and hematite; 4) remnant paint coats, formed by metallic zinc, and its products of alteration represented by zincite and hidrozincite. Through the results of this research it was possible to indicate the evolution of processes in iron architecture production, and enrich this research area with scientific information, as subside for future restorative processes.